Synthesis in solvent-free conditions, characterization and biological activity of a new Schiff-base ligand and its Cu(II) complex - Elmali, Fikriye Tuncel; Peksel, Ayseguel; Demirhan, Nebahat (TAYLOR & FRANCIS LTD, 2009)
A new bis-imine Schiff base (N8O2 donor, LH2) has been synthesized by melt condensation of 3-amino-1,2,4-triazole with 1,5-bis(2'-formylphenyl)-1,5-dioksapentane in 2 : 1 molar ratio, in solvent and solvent-free conditions. The ligand has been characterized using FTIR, UV-Vis, 1H NMR, 13C NMR, mass spectra, elemental analysis, and thermal (TGA-DSC) techniques. A new complex of LH2 with Cu(II) has been synthesized in solvent and solvent-free conditions. FTIR, UV-Vis mass spectra, and thermal analysis (TGA-DSC) have been used to characterize the Cu(II) complex. Thermal degradation showed that the final products were black carbon and metallic copper. Distorted octahedral geometry has been observed around CuLH2Cl2 center dot LH2 and its Cu(II) complex have been screened for in vitro antifungal and antioxidant activities. Antioxidation was determined for their superoxide scavenging and reducing activities. The ligand and its Cu(II) complex have strong antifungal activity against Aspergillus niger. The compounds have significant superoxide anion radical scavenging activity and reducing power against various antioxidant systems in vitro.
Keywords: Synthesis; Schiff base; Solvent-free reaction; Cu(II) complex; Antifungal activity; Antioxidant activity; ANTIBACTERIAL ACTIVITY; METAL-COMPLEXES; SALICYLALDEHYDE; 1,2,4-TRIAZOLE; EXTRACTS; Chemistry